Pemberdayaan dalam Meningkatkan Pemasaran dan Manajemen Usaha UMKM Younie Craft di Kelurahan Tegalrejo, Kota Salatiga - Pratiwi Jatining Putri; Divya Devi Arsita Syaharani; Elisa Agtrid Tivanka; Devi FItriyaningsih; Salma Navisa; Elvano Koni Bagaswara; Sri Mulyani; Dian Anjiliziani; Ulfi Ardiyani; Joko Pramono (Institut Teknologi dan Bisnis Semarang, 2025)
Tegalrejo Village, located in Argomulyo District, Salatiga City, has great potential in developing the local economy through the MSME sector. One of the MSMEs that is growing rapidly is Younie Craft, which produces handicraft products. However, this MSME faces various challenges, such as limited marketing, ineffective financial management, and limitations in operational management. For this reason, the Community Empowerment Practical Lecture (KPPM) program was carried out with the aim of providing assistance and solutions to overcome the problems that exist in Younie Craft. This assistance includes digital marketing training, simple bookkeeping, product innovation, and workspace layout arrangement to improve operational efficiency. The method used in this activity involves three stages, namely: (1) Preparation, which includes meetings with MSME owners and location observations; (2) Problem Analysis and Identification, where the team identifies key problems such as digital marketing, bookkeeping, product innovation, and layout arrangement; 3) Implementation, which includes providing solutions in the form of training and assistance in the fields of digital marketing, bookkeeping, product innovation, and layout arrangement. The results of this activity show significant improvements in terms of marketing through digital platforms, more structured financial management, and increased product quality and workspace efficiency. With this program, Younie Craft UMKM can increase competitiveness, expand the market, and make a positive contribution to the local economy in Tegalrejo Village.